Coaches’ Motivational Instruction and Athlete’S Learning in Running Sports - Chen, Yutong (International Journal of Social Sciences and Public Administration, 2024)
This study aimed to assess the progress made in training techniques and athlete performance at Tianjin University Sports in China, with a specific focus on sports other than traditional track events. Comprehending the effectiveness of training regimens that optimize the transfer of training impact was crucial. The study unveiled a heterogeneous sample regarding age, gender, and academic year. The male respondents slightly exceeded the number of females. Most respondents were in the age range of 16-17 years. The largest group consisted of first- and second-year students, followed by third- and fourth-year students. These findings indicate that the results of the study can be applied to comparable educational and community environments. The study revealed a noteworthy link (p-value < 0.05) between coaches’ motivating teaching and players’ learning assessments, albeit the coefficient was moderate (0.282). This suggests that although motivational tactics can influence the learning results of athletes, there may be other factors that also have important effects. To improve athlete training and performance, the study suggested using feedback mechanisms such as surveys, focus groups, and individual interviews to assess training satisfaction and determine motivating requirements. Also, the training of coaches in effective motivational approaches and the promotion of a supportive team atmosphere were given special importance. An optimized running sports training regimen was established, encompassing low-intensity runs, moderate-paced runs, high-intensity intervals, and extended runs to enhance stamina, velocity, and overall athletic performance. This program is supplemented with designated rest days and cross-training activities to facilitate recuperation and ensure well-rounded advancement.